Ukuran Perusahaan Memoderasi Pengaruh Leverage, Likuiditas dan Audit Tenure Terhadap Opini Audit Going Concern - Dicko Reynaldi Pasaribu; Ruswan Nurmadi (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This research aims to examine how leverage, liquidity, and audit tenure affect going concern audit opinions, with company size acting as a moderating variable in infrastructure companies listed on the Indonesia Stock Exchange from 2019 to 2023. This research uses a quantitative method, with purposive sampling as the sampling technique. The sample criteria obtained were 72 companies with a period of 5 years. The analysis techniques used in this study are Logistic Regression Analysis and Moderated Regression Analysis (MRA). The results of the analysis show that the three independent variables, namely leverage, liquidity, and audit tenure, do not affect the going concern audit opinion. Company size, which acts as a moderating variable, cannot moderate the relationship between leverage, liquidity, and audit tenure on the going concern audit opinion.